PHYTOCHEMICAL SCREENING AND ANTI-MICROBIAL ACTIVITY OF CINNAMON SPICE AGAINST URINARY TRACT INFECTION AND FUNGAL PATHOGENS: Pharmaceutical Science-Herbal Technology - AHUJA SHREYA; DHARMADIKARI MANISHA; JOSHI SONALI (International Journal of Life Science and Pharma Research, 2022)
There is an increasing apprehension among scientists regarding the use of chemical preservatives and synthetic antimicrobials. These chemicals used to inactivate or inhibit growth of pathogenic organisms in turn make them resistant to these antimicrobials over the time. Cinnamon (Cinnamomum verum) is well known in India as a food spice but little do people know that Cinnamon has an enormous potential as an antimicrobial agent and is a powerful antioxidant. Its abundant value in treating disorders like diabetes (Khan A. et al.2003), inflammation, ulcers (Jakhetia V. et al. 2010), Alzheimer’s (Peterson DW et al. 2009) have already been proven. We wanted to find out, through our study, if Cinnamon (in any of its three forms – bark, leaf or oil) has any effect on urinary tract infection isolates and fungal isolates, in an attempt to replace chemical drugs with nature’s products. Infected urine samples were used to isolate bacteria which were subjected to the antimicrobial assay of commercially available cinnamon oil and the extracts of cinnamon leaf and bark. The inhibitory effect was checked as a consequence on the growth curve of bacteria. The extracts were analyzed for phytochemicals which give cinnamon its antimicrobial property. Lastly, the antifungal property of cinnamon was tested on Aspergillus niger, a common food spoiling and disease causing fungus. The study showed that cinnamon oil is a more potent antimicrobial agent than any cinnamon extract and it has the potential for further research in drug development and as a food preservative.